2019
DOI: 10.1186/s13039-018-0413-1
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy of QF-PCR, CMA and karyotyping on a de novo case of mosaic isodicentric Y chromosomes

Abstract: BackgroundIsodicentric chromosomes are the most frequent structural aberrations of human Y chromosome, and usually present in mosaicism with a 45, X cell line. Several cytogenetic techniques have been used for diagnosing of uncommon abnormal sex chromosome abnormalities in prenatal cases.Case presentationA 26-year-old healthy woman was referred to our centre at 24 weeks of gestation age. Ultrasound examination indicated she was pregnant with imbalanced development of twins. Amniocentesis was referred to the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“…Furthermore, electronic platforms such as the TCGA database and cBioPortal displays the patterns of gene expression and clinical data from several clinical trials in (solid) malignancies. This allows universal access to genetic information, and thus can function as useful tools in the development of a genetic prognosticator for (future) prospective trials [ 136 , 137 ].…”
Section: The Tme In Scchnmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, electronic platforms such as the TCGA database and cBioPortal displays the patterns of gene expression and clinical data from several clinical trials in (solid) malignancies. This allows universal access to genetic information, and thus can function as useful tools in the development of a genetic prognosticator for (future) prospective trials [ 136 , 137 ].…”
Section: The Tme In Scchnmentioning
confidence: 99%
“…SCCHN is considered one of the (tobacco-related) solid malignancies with the highest TMB, around 5-10mut/MB [ 20 ]. Several clinical trials confirmed that presence of high TMB was correlated to better prognosis when treated with ICI [ 137 , 138 , 141 , 142 ]. However, this was mostly in case of virus-negative (HPV − /EBV − ) SCCHN, which have higher TMB due to prevalence of secondary risk factors (smoking/alcohol consumption).…”
Section: The Tme In Scchnmentioning
confidence: 99%
“…Such large changes are often needed during cancer development, as the tumour experiences stresses that need to be overcome in order to survive; such stresses include chemotherapy and immune pressure) [69, 70]. In such a context, rapid genome-wide changes are often more effective in inducing adaptation than single gene mutation, as large genomic rearrangements/changes lead to a change in genome organisation, interactions between genes, and the transcriptome, therefore leading to a significant change in phenotype [71]. While not every genomic rearrangement leads to a viable karyotype, the added ITH introduced by CIN is thought to increase the probability of a viable karyotype within the population [70].…”
Section: Introductionmentioning
confidence: 99%
“…Such examples of events of punctuated evolution or macroevolution have been observed in cancer [7274]. Following a burst of punctuated evolution, subsequent single gene mutations could then further fine-tune the selected karyotypes to reach optimal growth and survival (for a more in-depth review on the relationship between CIN and cancer evolution, see References [71, 75]).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the limitation of each technique, using one single method to identify isodicentric Y chromosomes could be quite risky, especially when it coexists with other cell lines. A combination of cytogenetic and molecular analysis would provide detailed information on the gain and loss of isodicentric Y chromosomes, assisting in the interpretations of the test results [19]. However, inconsistent results might arise in cases of very complicated mosaicism, which require apanoramic view of the results in a retrospective manner [17].…”
Section: Discussionmentioning
confidence: 99%